The law of self defense the indispensable guide for the armed citizen - Branca, Andrew F. (Law of Self Defense, 2016)
You're prepared to protect yourself and your loved one ... now arm yourself for the legal battle that happens after an attack. Branca teaches you how to make quick, effective legally appropriate decisions in life-or-death situations. True life examples of people defending themselves, and how their decisions helped, hurt, or even destroyed their case, are included.